PENGARUH KECERDASAN EMOSIONAL DAN PEMANFAATAN SISTEM INFORMASI MANAJEMEN TERHADAP PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DASAR DI UPTD KECAMATAN TAMPAN KOTA PEKANBARU - Beni Saputra; Jimmi Copriady; Sumardi Sumardi (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
This study aims to analyze the effect of variables (1) emotional intelligence ondecision making, (2) utilization of management information systems on decision making, (3)emotional intelligence and management information system utilization together to decision making.The sample of research is Head of Primary School at UPTD Kecamatan Tampan PekanbaruCity amounted 52. Data obtained by spreading of questionnaire using likert scale. To test thevalidity of research instruments used Product Moment analysis, while for reliability test usedAlpha Cronbach. Data analysis used descriptive analysis, inferential statistical analysis forhypothesis testing. The results showed a positive and significant influence between emotionalintelligence on decision making of 0.581, and there is a positive and significant influence betweenthe utilization of management information systems to decision making of 0.513. While the influenceof emotional intelligence and utilization of management information systems on decision makingof 0.607.